Penggunaan teknologi komunikasi sebagai upaya penyelamatan ibu dan bayi baru lahir di kabupaten karawang - Siti Nursanti (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
Because the health of maternal and neonatal is a shared responsibility, every region in Indonesia, including Karawang District, makes efforts to rescue mothers and babies. The purpose of this study is to determine the extent of the Karawang District Government's ability to save mothers and babies via the use of a networked communication system known as SijariEMAS. This research utilizes a case study methodology, which is a qualitative research method that attempts to integrate phenomena and further investigate a case in order to construct a narrative capable of answering the why and how questions. The findings of this study include the existence of SiJariEMAS, a communication and information technology system that connects all health facilities in Karawang Regency and is capable of connecting health workers who will refer mothers who are facing an emergency, exchange information simultaneously, and take the best action to save the mother and baby. New communication technology, like an internet-based communication and information system, adds another dimension to the traditional health sector and makes it easier for health professionals to help try to save mothers and babies.